2009
DOI: 10.1007/s11356-009-0150-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of products formed via photolysis of decabromodiphenyl ether

Abstract: BDE-209, the main constituent of DecaBDE, is primarily forming debrominated diphenyl ethers with higher persistence which are more bioaccumulative than the starting material when subjected to UV light. Hence, DecaBDE should be considered as a source of these PBDE congeners in the environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 49 publications
4
42
0
Order By: Relevance
“…Previous studies have found that the smaller the quantity of bromide in PBDEs, the faster the degradation (of the PBDEs) through biodegradation [11] or photolysis [14]. The results from our study showed that about 40% of the BDE 15 underwent declining extractable concentration, while no dissipation of BDE 209 was observed.…”
Section: Bde 209 and Bde 15 Degradation In Soil Samplessupporting
confidence: 51%
See 1 more Smart Citation
“…Previous studies have found that the smaller the quantity of bromide in PBDEs, the faster the degradation (of the PBDEs) through biodegradation [11] or photolysis [14]. The results from our study showed that about 40% of the BDE 15 underwent declining extractable concentration, while no dissipation of BDE 209 was observed.…”
Section: Bde 209 and Bde 15 Degradation In Soil Samplessupporting
confidence: 51%
“…Among the 209 PBDE congeners, 2,2 ,3,3 ,4,4 ,5,5 ,6,6 -decabromodiphenyl ether (BDE 209) is the primary component in a commonly used flame retardant, which constitutes approximately 80% of the worldwide use of PBDEs. Moreover, BDE 209 has been shown to be a source of lower brominated diphenyl ether congeners [13][14][15]. As potential degradation products of higher BDEs in the environment, it is necessary to take into account its effect on the soil microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…PBDE congeners may undergo photolysis Christiansson et al, 2009) and reductive debromination Granelli et al, 2010) but are less sensitive to nucleophilic aromatic substitution (NAS) and oxidations (Rahm et al, 2005;Moreira Bastos et al, 2008). However, BDE-209 undergoes NAS.…”
Section: Chemical Characteristicsmentioning
confidence: 99%
“…The widespread use of PBDEs in items commonly found in homes leads to contamination of the indoor environment, particularly of household dust (12,13). Once in the environment, PBDEs can debrominate to form lower BDE congeners and can also form other products, such as bromophenols, furans and dioxins (14)(15)(16)(17)(18)(19). The relevance of debromination to human exposure may be most pronounced for BDE-209, the dominant congener in dust (20,21).…”
Section: Introductionmentioning
confidence: 99%